The effects of double folding cluster model potential on some astrophysical reactions - Abdul Aziz, Azni; Yusof, Norhasliza; Firihu, Muhammad Zamrun; Abu Kassim, Hasan (IOP Publishing, 2015)
The Double Folding Cluster Model Potential is constructed using the α - cluster structure of nuclei. It can be derived by folding an α − α interaction with density distributions of α - clusters inside the projectile and target nuclei. This potential has been successfully tested on elastic scattering data of some selected nuclei. In this work, we are interested to investigate the implications of this potential on astrophysical aspects.